The Haunting of Sunshine Girl - Paige McKenzie
Based on the wildly popular YouTube channel, The Haunting of Sunshine Girl has been described as (3z (BGilmore Girls meets Paranormal Activity for the new media age.(3y (BYA fans new and old will learn the secrets behind Sunshine$1 (Bthe adorkable girl living in a haunted house$1 (Ba story that is much bigger, and runs much deeper, than even the most devoted viewer can imagine$1! =s